Foodborne Pathogens and Antibiotic Resistance in School Meals: Implications for Public Health - Muhammad, Shamsudeen; Tomo, Farida Abubakar; Mungadi, Lauratu Samaila (CV. Literasi Indonesia, 2025)
Food safety is a critical public health concern, particularly in school feeding programs, where improper handling and contamination pose significant health risks. This study investigates the bacteriological quality and antibiotic susceptibility patterns of Escherichia coli isolates from food samples obtained from two boarding schools in Zuru, Kebbi State, Nigeria. A total of 12 food samples were analyzed for microbial contamination, with Total Plate Count (TPC), Coliform Count, and Salmonella Count determined using standard bacteriological methods. The antibiotic susceptibility patterns of E. coli isolates were assessed using the disk diffusion method. The TPC ranged from 2.6 × 10³ to 5.6 × 104 cfu/g in FSTC Zuru and 2.5 × 10³ to 8.0 × 10³ cfu/g in GSTC Zuru. Coliform counts ranged from 2.0 × 10² to 9.3 × 10² cfu/g, while Salmonella counts varied between 1.0 × 10¹ and 4.0 × 10¹ cfu/g. Escherichia coli, Salmonella, Shigella, Staphylococcus aureus, and Klebsiella pneumoniae were identified among the isolates, with E. coli and Salmonella each accounting for 33.3% of isolates. Antibiotic susceptibility testing of E. coli isolates revealed high resistance to Amikacin (100%), Streptomycin (75%), and Tetracycline (62.5%), while full susceptibility was observed for Gentamicin and Cefotaxime (100%). These findings highlight the microbial risks associated with school feeding programs and the prevalence of antibiotic-resistant bacteria, emphasizing stringent food safety measures, improved hygiene practices, and routine surveillance to mitigate foodborne infections and the spread of resistant pathogens.